METHODOLOGY FOR DEVELOPING AESTHETIC TASTE BASED ON NATIONAL VALUES - Rahimova Gulhayo Qahramonovna (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This article examines the methodological foundations of developing students’ aesthetic taste through national values in visual arts education. It highlights the role of cultural heritage, traditions, and folk art in shaping learners’ sense of beauty, harmony, and artistic perception. The research emphasizes that aesthetic education rooted in national identity helps students appreciate their cultural roots while developing universal artistic sensitivity. The integration of national motifs, colors, and symbols into art lessons strengthens both the aesthetic and moral dimensions of education. The paper proposes practical strategies for fostering aesthetic awareness, emotional intelligence, and creative thinking among students through art activities grounded in national values.